2015
DOI: 10.1002/masy.201400081
|View full text |Cite
|
Sign up to set email alerts
|

Potential Antibacterial Activity of Polystyrene Nanoparticles/Chitosan Coated on Cotton Fabrics

Abstract: Summary: This research is to study the potential of using polystyrene nanoparticles and chitosan solution to increase the anti-bacterial activity on cotton fabrics prepared by a conventional pad-dry-cure method. Firstly, cotton fabrics were coated with chitosan solutions at the concentrations of 0.1, 0.5, and 1.0 (%w/v) and tested for the antibacterial property which was determined by clear zone measurement and viable count assay using Escherichia coli (ATCC 25922) as a tested microorganism. The results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…In addition, the chitin/chitosan also can bind with bacteria DNA subsequently disrupting its DNA replication or it can impair the ability of ribosomes to transcribe messenger´s RNA (Huang et al, 2012). Similar phenomenon was also observed and reported elsewhere (Annur et al, 2015;Inamdar and Mourya, 2014;Li et al, 2013;Rodríguez-Núñez et al, 2012;Siralertmukul et al, 2015). Glucan in chitin/chitosanglucan complex had antibacterial activity against different types of bacteria and fungi (AL TUWAIJRI et al, 1987;Bohn and BeMiller, 1995;di Luzio et al, 1979;Guyard et al, 2002;Kagimura et al, 2015;Kokoshis et al, 1978;Luzio et al, 1980;Talbott and Talbott, 2009).…”
Section: Antibacterial Performance Of Chcsgc Wound Dressingsupporting
confidence: 61%
“…In addition, the chitin/chitosan also can bind with bacteria DNA subsequently disrupting its DNA replication or it can impair the ability of ribosomes to transcribe messenger´s RNA (Huang et al, 2012). Similar phenomenon was also observed and reported elsewhere (Annur et al, 2015;Inamdar and Mourya, 2014;Li et al, 2013;Rodríguez-Núñez et al, 2012;Siralertmukul et al, 2015). Glucan in chitin/chitosanglucan complex had antibacterial activity against different types of bacteria and fungi (AL TUWAIJRI et al, 1987;Bohn and BeMiller, 1995;di Luzio et al, 1979;Guyard et al, 2002;Kagimura et al, 2015;Kokoshis et al, 1978;Luzio et al, 1980;Talbott and Talbott, 2009).…”
Section: Antibacterial Performance Of Chcsgc Wound Dressingsupporting
confidence: 61%
“…First, cotton fabrics were coated with chitosan solutions at concentrations of 0.1, 0.5, and 1.0 (%w/v), and chitosan/cotton fabrics were then coated with polystyrene nanoparticle solution; the bacterial reduction rates of chitosan/polystyrene nanoparticles/cotton fabric were 90.3%, 90.8%, and 65.5%, respectively. The results showed that the antibacterial activity of cotton fabric can be improved by coating the cotton fabric with polystyrene nanoparticles and then chitosan . Poly­( N -isopropylacrylamide)/chitosan hydrogel was used to improve the antibacterial activity of cotton fabric; the bacterial reduction of poly­( N -isopropylacrylamide)/chitosan/cotton fabric on S.…”
Section: Applications Of Chitosan and Its Derivatives In Antibacteria...mentioning
confidence: 99%
“…The results showed that the antibacterial activity of cotton fabric can be improved by coating the cotton fabric with polystyrene nanoparticles and then chitosan. 166 Poly(N-isopropylacrylamide)/chitosan hydrogel was used to improve the antibacterial activity of cotton fabric; the bacterial reduction of poly(N-isopropylacrylamide)/ chitosan/cotton fabric on S. aureus and E. coli was more than 99%. 167 Chitosan can also be combined with metals or metal oxides to modify the fabric to improve the antibacterial activity of the fabric.…”
Section: Applications Of Chitosan and Its Derivatives In Antibacteria...mentioning
confidence: 99%
“…However, they reveal a number of different geometries in detail and a variety of density profiles from the center to the surface. Nevertheless, due to the merits based on nanoscale dimensions, nanoparticles have led to emerging applications in various fields, such as smart coatings, coating additives, polymers, agrochemicals, detergents, lubricants, cutting oils, corrosion inhibitors, catalysts, chemical storage, environmental remediation, energy generation and storage, electro-optics, photonics, microelectronics, cosmetics, pharmaceutics, biosensors, medical diagnostics, medical therapy, drug delivery carriers, foods, and so on [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…For a material, all properties are generally known to depend upon the morphological structure and molecular characteristics. In the case of nanoparticles, the properties and performance are also highly dependent upon the morphology details as well as the chemical characteristics [1,[7][8][9][10][11][12][13][14]. The morphology details include three-dimensional geometry, surface texture, size and size distribution, surface-to-volume ratio, and density gradient profile.…”
Section: Introductionmentioning
confidence: 99%